Collaborative configuration of renewable energy and energy storage under fixed investment in the decarbonization process - Jinlin Liao; Jinlin Liao; Guilian Wu; Guilian Wu; Guilian Wu; Jinghao Li (Frontiers in Energy Research, 2024)
In the process of decarbonization, the configuration of renewable energy and energy storage plays a crucial role. In current research, there is often a singular focus on the isolated optimization of either renewable energy configurations or energy storage configurations, resulting in limitations within the optimized outcomes. Therefore, we propose a collaborative configuration approach for renewable energy and energy storage under fixed investment, considering the impact of uncertainty on optimization results. By employing the W/S (wind-to-solar ratio) and E/P (energy-to-power ratio) and constructing a model with an hourly granularity, we can obtain the configurations of renewable energy and energy storage at crucial time points. Using the UK as a case study, we calculate the configurations for renewable energy and energy storage from 2020 to 2050, offering effective recommendations for the decarbonization efforts in the UK.